Analysis of Democratic Party Political Imagery Communication on Social Media in 2024 - Mauliana, Tiara Friska; Harahap, Nursapia (Formosa Journal of Multidisciplinary Research, 2024)
The ways in which technology has impacted human life are numerous. Social media is one of the most widely used technical innovations. These days, social media is an integral part of politics, not just for the general public. Social media provides a platform for political players to garner positive support. It is also true that social media can readily become a boomerang that can harm someone's political image at any time by easily stemming a favorable image. The examination of how the Democratic Party uses political communication to shape its public image, particularly on social media platforms, is the main emphasis of this essay. by employing a descriptive technique, which entails reading references from other books. This article will discuss how the Democratic Party uses social media. Moreover, in reference to the political communication employed. Finally, it can be said that social media plays a significant role in establishing the party's image and serving as a platform for campaigning.